Behavioral Cost of Managerial Decisions Under Risk Perception and Culture: A Comparative Study Between the United States and Pakistan. (July 2021) - Dar, Nishwa Iqbal; Shah, Syed Zulfiqar Ali; Ahmed, Zeeshan
The study is an attempt to find the reasons for biased behavior of overconfident managers while making financial decisions on behalf of shareholders. The study further seeks the ways to resolve the problems faced by firms due to such biased decision-making. For this purpose, quantitative research method is used to uncover the new information for better understanding of study. The comparative analysis has been done through survey-based data collected from executives/managers of firms listed on Pakistan Stock Exchange and New York Stock Exchange. The results indicate that overconfidence bias plays a significant role in managerial decisions for Pakistan compared with U.S. managers. This study applied mediation and moderation tests and found the significant mediating role of risk perception for overconfidence bias and manager decisions. The study further checked moderating role of cultural value, that is, the role of uncertainty avoidance between overconfidence bias of managers and risk perception. Hence, the role of cognitive biases and bounded rationality is undeniable for managerial decision-making and ultimate behavioral cost that firms have to pay due to undesired outcomes of situations. Consequently, this study has reached to extract the hidden facts and solutions to the observed issues for developed and emerging economy's firms through cultural differences.